2000
DOI: 10.1111/j.1365-2621.2000.tb13584.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Acetic and Propionic Acids from Chitosan‐based Antimicrobial Packaging Films

Abstract: The diffusion of acetic or propionic acids from thin (44 to 54 mm) chitosan-based antimicrobial packaging films in which they were incorporated was measured after immersion of the films in water, and the effects of pH (5.7, 6.4, or 7.0) and temperature (4°C, 10°C, or 24°C) on diffusion were investigated. The kinetics of acetic-and propionic-acid release deviated from the Fickian model of diffusion. Diffusion was found to be unaffected by pH in the range of values tested, but a decrease in temperature from 24°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
0
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(142 citation statements)
references
References 33 publications
5
115
0
11
Order By: Relevance
“…It has been suggested that this activity is caused by the presence of phenolic compounds and monoterpenes [20]. The phenolic components weaken the phospholipid bilayer of the cell membrane, causing an increase in permeability and leakage of the intracellular components [17]. Pandima et al, [42] reported that primary mechanism of action of eugenol is disruption of the cytoplasmic membrane, which increases its non-specific permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that this activity is caused by the presence of phenolic compounds and monoterpenes [20]. The phenolic components weaken the phospholipid bilayer of the cell membrane, causing an increase in permeability and leakage of the intracellular components [17]. Pandima et al, [42] reported that primary mechanism of action of eugenol is disruption of the cytoplasmic membrane, which increases its non-specific permeability.…”
Section: Discussionmentioning
confidence: 99%
“…A packaging system that allows for the slow release of an antimicrobial agent into the food could significantly increase the shelf life and retain the quality of a variety of foods [14]. Several articles have reported the use of antimicrobial agents to formulate antimicrobial packaging [6,[13][14][15][16][17][18]. Essential oils and their components have antimicrobial properties against microorganisms (including Gram-positive and Gram-negative bacteria) [13,14,16,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A rastreabilidade é uma ferramenta utilizada para garantir a segurança e qualidade do produto; no caso de alimentos, a segurança alimentar e para fármacos, a ação do composto bioativo. As indústrias de embalagens estão buscando novos métodos objetivos, realizáveis e de custo efetivo, que mantenham a integridade do produto, visando garantir qualidade e segurança [1] , e a confiança do consumidor [2] .…”
Section: Introductionunclassified
“…A rastreabilidade é uma ferramenta utilizada para garantir a segurança e qualidade do produto; no caso de alimentos, a segurança alimentar e para fármacos, a ação do composto bioativo. As indústrias de embalagens estão buscando novos métodos objetivos, realizáveis e de custo efetivo, que mantenham a integridade do produto, visando garantir qualidade e segurança [1] , e a confiança do consumidor [2] .Embalagens inteligentes consistem em sistemas onde é possível a comunicação com o consumidor, de informações relacionadas à qualidade e segurança do produto através da embalagem. Isto envolve a incorporação de sensores ou indicadores que respondem por sinal (elétrico, colorimétrico, etc.)…”
unclassified
“…Availability of nutrients and moisture, and favorable temperature during germination contributes the rapid growth of microbes causing foodborne diseases as well as reducing the shelf life of sprouts (16). Antimicrobial coated films may be an efficient alternative to prevent microbial growth leading to spoilage of sprouts since the active ingredient may selectively and gradually migrate from the package to the head space for a extended period of time (17).…”
Section: Introductionmentioning
confidence: 99%